Understanding humour as a dimension of affective and cognitive competencein patients diagnosed with paranoid schizophrenia - Żmuda, Diana; Bereza, Bernarda; Urbańska, Anna; Orzeł-Górniak, Małgorzata; Makara-Studzińska, Marta; Olajossy, Marcin (Current Problems of Psychiatry, 2015)
The aim of our study was to analyze the ways of thinking of patients diagnosed with paranoid schizophrenia, and compare this with that of healthy individuals. This was done by ascertaining their reception and interpretation of the positive affective impulses induced by way of the core dimensions of humour: comicality and level of understanding of jokes. The study involved a group of 22 persons, including 11 patients diagnosed as having paranoid schizophrenia, and who are being treated in The Second Psychiatry and Psychiatric Rehabilitation Department in Lublin. The other 11 persons, without any clinical diagnosis (never treated by psychiatrists), serve as a control group. The research material was gathered based on standard methods of neuropsychological assessment: sub-tests of the WAIS-R (PL) battery, including “span forward”,” span backward”, “vocabulary” and “understanding”. This method of testing was chosen because the multidimensional construct of the sense of humour requires great intellectual capacity, suitable cognitive function and adequate affective competences. The analysis was complemented by data gathered from a study questionnaire designed for assessing the level of understanding of chosen emotional contents presented in the form of jokes. Jokes were chosen as the means of measurement, because we felt that the reaction to these to be the simplest way of comparing the exhibition of a sense of humour. The results clearly indicate that persons afflicted with paranoid schizophrenia assessed the comicality of the presented jokes at a significantly lower level. Moreover, they demonstrated a lower level of adequacy of their understanding. These recognized deficits may imply a correlation between lowered level of perception and interpretation of comical affective contents, and the core cognitive restrictions and negative emotional symptoms observed more often in persons with paranoid schizophrenia.